PENGARUH KECEPATAN ARUS PENGELASAN DAN PANAS MASUK TERHADAP SIFAT MEKANIS LOGAM LAS PADA PENGELASAN SAW BAJA KARBON ASTM A 29 - Duniawan, Agus; -, Sutrimo (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
Welding is a joining technique in production process which weld two metals or more using heat energy Physical property near welding zone changes in microstructure, deformation and thermal stress in order to minimize a negative effects, it is required a correct procedure in welding, selection of optimum welding current and heat input. Welding joint in steel countruction or pressure vessel has to fullfill the welding standard such as, high stress property 27 joule for temperature – 50oC and 100 joule for 0oC. The aim of this research is to investigate the Effect of variation in welding current, welding speed and heat input on microstructure of main metal and HAZ. Experimental work is done using optic microscope, hardness test and univercal machine. The purpose of the research is to obtain optimum welding parameter related which micro structure and mechanical properties of weld metal and HAZ. The variation in heat input are 2 kg/mm, 3kg/mm, 4kg/mm. The variation of welding speed are 7 mm/s, 4,7 mm/s and 3,5 mm/s at current of 400 Ampere,mean while at 600 Ampere the variation in welding speed are 10,5mm/s, 7mm/s, 5,25mm/s. The result shaws that microstructure is dominated by ferit size and ferit Widmanstatten. The highest hardness of 164,98 VHN is found at welding zone of specimen A with welding current of 400 Amper, welding speet of 7 mm/s and heat input of 2kg/mm. Tension and yielding stress of 567 and 472 MP occur for specimen A1 with 600 Ampere welding speed of 7 mm/s and heat input of 2kg/mm.